2016
DOI: 10.1371/journal.pone.0159252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Mediterranean Diet on Cardiovascular Outcomes—A Systematic Review and Meta-Analysis

Abstract: BackgroundA Mediterranean dietary pattern is widely recommended for the prevention of chronic disease. We sought to define the most likely effects of the Mediterranean diet on vascular disease and mortality.MethodsWe searched MEDLINE, EMBASE and the Cochrane Central Register without language restriction for randomized controlled trials comparing Mediterranean to control diets. Data on study design, patient characteristics, interventions, follow-up duration, outcomes and adverse events were sought. Individual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
99
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(111 citation statements)
references
References 31 publications
6
99
1
5
Order By: Relevance
“…For SRMAs of observational studies, dietary patterns were Mediterranean diet (eight SRMAs), DASH diet (three SRMAs), diets with high HEI and AHEI scores (two SRMAs), HEI/AHEI and cardiovascular health (CVH) scores (one SRMA), and Diet Inflammatory Index (DII) scores (one SRMA). For SRMAs of RCTs, the interventions were prescribing a Mediterranean diet (one SRMA) [18] and modifying diet…”
Section: Dietary Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…For SRMAs of observational studies, dietary patterns were Mediterranean diet (eight SRMAs), DASH diet (three SRMAs), diets with high HEI and AHEI scores (two SRMAs), HEI/AHEI and cardiovascular health (CVH) scores (one SRMA), and Diet Inflammatory Index (DII) scores (one SRMA). For SRMAs of RCTs, the interventions were prescribing a Mediterranean diet (one SRMA) [18] and modifying diet…”
Section: Dietary Patternsmentioning
confidence: 99%
“…For SRMAs of observational studies, dietary patterns were Mediterranean diet (eight SRMAs), DASH diet (three SRMAs), diets with high HEI and AHEI scores (two SRMAs), HEI/AHEI and cardiovascular health (CVH) scores (one SRMA), and Diet Inflammatory Index (DII) scores (one SRMA). For SRMAs of RCTs, the interventions were prescribing a Mediterranean diet (one SRMA) [18] and modifying diet quality by lowering the consumption of carbohydrates, fat, and calories, and increasing the consumption of fish, vegetables, complex carbohydrates, and fiber (two SRMA) [17,19]. Most of the SRMAs (16/18) considered the general population as the study's participants, while two included only high-risk populations (e.g., patients with obesity, hypertension, and DM).…”
Section: Dietary Patternsmentioning
confidence: 99%
“…The Mediterranean diet, high in fruits, vegetables, nuts, cereals, fish, and olive oil with moderate red wine consumption and minimal amounts of red meat and dairy products has been linked to beneficial effects on vascular disease, blood pressure, glycemic control, and lipids (76, 77). However, evidence is limited and variable regarding cardio-protection from diet in the general population (78), and almost nonexistent in patients receiving trastuzumab specifically. Aggressive glycemic control is also recommended in guidelines despite a paucity of evidence that this will decrease heart failure risk.…”
Section: Preventing Trastuzumab-induced Cardiotoxicitymentioning
confidence: 99%
“…Much of the recent data on the effects of plant-based diets on CVD risk come from studies of vegetarian or semi-vegetarian diets (which allow the inclusion of fish and/or up to two servings of chicken per week) (Appleby & Key 2015;Wang et al 2015;Dinu et al 2016) or MedDs (Bloomfield et al 2016;Garcia et al 2016;Godos et al 2016;Liyanage et al 2016;Nissensohn et al 2016).…”
Section: Cardiovascular Disease and Plant-based Dietsmentioning
confidence: 99%
“…Details of the main studies that have evaluated the association between plant-based dietary regimes (both vegetarian and MedD) and cardiovascular heath are detailed in Table 1 (Key et al 1999;Appleby et al 2016 ;Crowe et al 2011;Buckland et al 2009;Key et al 2003;Key et al 2009;Lopez-Garcia et al 2014;Mart ınez-Gonz alez et al 2014). In a recent review of RCTs comparing MedDs to control diets, individual studies were pooled to create summary estimates for the RR of the diets on major vascular events and vascular deaths (Liyanage et al 2016). Five studies (n = 9950) were identified which when pooled showed a protective effect of a MedD against major vascular events (RR 0.69, 95% CI: 0.55, 0.86) and stroke (RR 0.66; 95% CI: 0.48, 0.92) but not cardiovascular mortality (RR 0.90: 95% CI: 0.72, 1.11).…”
Section: Cardiovascular Disease and Plant-based Dietsmentioning
confidence: 99%